Analisis Sanksi Terhadap Pelaku Jarimah Penganiayaan Berencana Dalam Perspektif Hukum Pidana Islam - Alifia Nur Basanti; Fadlah Khairunnisa; Fadlli Naufal Rahim; Farrel Ar Rasyid; Deden Najmudin (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Torture is an act of physical injury but not to the point of loss of life or death. Persecution is divided into intentional or planned abuse and unintentional. The focus of this research is on intentional or planned abuse. This social phenomenon regarding premeditated abuse is an act that violates Islamic law. Therefore, cases of planned abuse must be followed up immediately and become an urgency in this research. The aim of this research is to analyze the sanctions received by perpetrators of planned abuse from the perspective of Islamic Criminal Law. The research method used in this research is the library research method with a normative juridical research approach and qualitative data analysis. The results of this research show that (1) If the abuse occurs intentionally or premeditated, in accordance with sharia law, the punishment is Qishas on the basis of Surah Al-Maidah verse 45 that Qishas is a balanced and appropriate penalty imposed on the perpetrator of the crime of intentional or premeditated abuse as The main punishment and if the victim's family forgives, then the punishment is changed to Diat which can then be replaced again with the Ta'zir punishment. (2) The provision of sanctions for planned persecution in Islamic criminal law upholds the principles of justice and the usefulness of sanctions. By imposing appropriate and fair punishments, and ensuring that these sanctions are beneficial to society, Islamic criminal law is able to create a safe and just environment.